Venetianske glas fra Vallensgård, Bornholm - Sode, Torben (Hikuin, 2010)
Glasses from Vallensgaard By Torben Sode In 1937 the wings of Bornholms largest farmhouse, Vallensgaard, burned down and in connection with the subsequent rebuilding of the farm the foundations of two older buildings were investigated. This work revealed that the foundations were the remains of the houses built just before 1560 by the former district bailiff Schweder Ketting, a rich merchant and brewer from the Hanseatic town of Lübeck. At the bottom of the foundation of the tower built onto the western wall of the southern building nearly 150 fragments of glass were found. They included 30 window glasses, some still with marks from the lead framing, together with more than 70 shards from at least four pear-shaped bottles, and more than 30 shards of so-called »waldglas«, mostly from vessels known as passglas. The most remarkable findings among the glass from Vallensgaard were the fragments of two filigree glasses in Venetian style. One, a trumpet-shaped foot with the rim folded under, was made of 52 twisted filigree canes made of white and clear glass. The second was a fragmented bowl from a filigree goblet. The bowl was decorated on the lower part with seven white threads alternating with seven twisted filigree canes vertically applied. Over these were two rows of a white filigree cane between two white canes applied horizontally. The two glasses in Venetian style were most probably made in glass workshops in Antwerp or London around 1550 and are in this way examples of very early glass produced à la façon de Venise.